(untitled) (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
On the occasion of the Day of Bulgarian Language and Culture 24th of May and as part of the St. Kliment’s Days, the Faculty of Classical and Modern Languages at Sofia University organized a poetry translation competition from a foreign language into Bulgarian under the title “The World is Within Us Through Language and Writing.” The lecturers in Norwegian at the Scandinavian Studies Programme provided one of the most lyrical poems by the renowned Norwegian poet, writer, and translator of poetry and drama, Inger Hagerup, for the competition. The poem, Two Tongues (To tunger), is from the collection Stanza with the Wind (Strofe med vinden, 1959).